Strategi adaptasi petani padi kecil terhadap perubahan iklim di Kabupaten Polewali Mandar - Hikmah, Aulia Nurul; Astaman, Putra; Mulaputri Ma'mur, Sitti Hardiyanti; Dassir, Muhammad; Nadirah, Sitti (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2025)
Farmers who own small-scale land are vulnerable to being threatened by climate change, because they do not have enough resources to cope with it. To minimize the negative impacts of climate change, farmers must implement adaptation strategies. This study aims to analyze the adaptation strategies applied by smallholder rice farmers in Polewali Mandar Regency. This research was conducted in Bunga-Bunga Village, Matakali District, Polewali Mandar Regency. Sample determination was carried out using the Slovin approach with a total of 30 respondents who owned small-scale rice farmers. The analysis method used is a qualitative approach with descriptive research. The results showed that age, education, dependents of the head of the family, length of farming, side jobs, land area, and land status affect the implementation of adaptation strategies to climate change. The adaptation strategies applied by smallholder rice farmers in Bunga-Bunga Village are survival strategies and consolidation strategies.